Let's do some calculus! (50)

Calculus Level 5

0 1 { ( 1 ) 1 / x 1 x } d x \large \int_0^1 \left\{(-1)^{\left\lfloor 1/x \right\rfloor}\cdot \frac 1x \right\} \ \mathrm{d}x

If the value of the above integral can be represented as a + ln ( b π ) a + \ln \left( \dfrac b\pi \right) for positive integers a a and b b , find a + b a+b .

Notations:


For more problems on calculus, click here .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

First Last
Jun 15, 2017

0 1 { ( 1 ) 1 x 1 x } d x = 1 ( 1 ) x x ( 1 ) x x x 2 d x by 1 x x \displaystyle \int_0^1 \left\{(-1)^{\left\lfloor \frac{1}{x}\right\rfloor}\cdot\dfrac{1}{x}\right\}dx = \int_{1}^{\infty}\frac{(-1)^{\lfloor x\rfloor}x - \lfloor (-1)^{\lfloor x\rfloor}x\rfloor}{x^2}dx\quad\text{ by }\frac{1}{x}\rightarrow x

Split into regions of floor(odd.xyz) = odd and floor(even.xyz) = even

n = 1 2 n 1 2 n 1 x d x + 2 n 2 n + 1 1 x d x n = 1 2 n 1 2 n 2 n x 2 d x + 2 n 2 n + 1 2 n x 2 d x = \displaystyle\sum_{n=1}^{\infty}\int_{2n-1}^{2n}\frac{-1}{x}dx+\int_{2n}^{2n+1}\frac{1}{x}dx-\sum_{n=1}^{\infty}\int_{2n-1}^{2n}\frac{-2n}{x^2}dx+\int_{2n}^{2n+1}\frac{2n}{x^2}dx =

n = 1 ln ( 2 n ) + ln ( 2 n 1 ) + ln ( 2 n + 1 ) ln ( 2 n ) + n = 1 2 n 2 n 1 + 2 n 2 n + 1 2 = \displaystyle\sum_{n=1}^{\infty}-\ln{(2n)}+\ln{(2n-1)}+\ln{(2n+1)}-\ln{(2n)} + \sum_{n=1}^{\infty}\frac{2n}{2n-1}+\frac{2n}{2n+1}-2 =

ln ( n = 1 1 1 4 n 2 ) + n = 1 1 2 n 1 1 2 n + 1 \ln{\big( \prod_{n=1}^{\infty}1-\frac1{4n^2}\big)} + \sum_{n=1}^{\infty}\frac{1}{2n-1}-\frac{1}{2n+1}

n = 1 1 1 4 n 2 = 2 π \displaystyle\prod_{n=1}^{\infty}1-\frac1{4n^2} = \boxed{\frac{2}{\pi}} from the Wallis Product

n = 1 1 2 n 1 1 2 n + 1 = n = 1 0 1 ( y 2 ) n 1 d y ( y 2 ) n d y = 0 1 n = 1 ( y 2 ) n 1 d y ( y 2 ) n d y = \displaystyle\sum_{n=1}^{\infty}\frac{1}{2n-1}-\frac{1}{2n+1} = \sum_{n=1}^{\infty}\int_{0}^{1}(y^2)^{n-1}dy-(y^2)^ndy =\int_{0}^{1}\sum_{n=1}^{\infty}(y^2)^{n-1}dy-(y^2)^ndy =

0 1 1 1 y 2 ( 1 1 y 2 1 ) = 1 \displaystyle\int_{0}^{1}\frac{1}{1-y^2}-( \frac{1}{1-y^2}-1) = \boxed{1}\quad by noticing the infinite geometric sequence and reversing the sum and integral. ln 2 π + 1 \displaystyle\ln{\frac{2}{\pi}}+1

You made a mistake here

n = 1 ( 2 n 1 2 n 1 x d x + 2 n 2 n + 1 1 x d x ) = n = 1 ( ln ( 2 n ) + ln ( 2 n 1 ) + ln ( 2 n + 1 ) ln ( 2 n ) ) = n = 1 ln ( 4 n 2 1 4 n 2 ) = ln ( n = 1 4 n 2 1 4 n 2 ) = ln ( 2 π ) \begin{aligned} \sum_{n=1}^{\infty} \left( \int_{2n-1}^{2n} \dfrac{-1}{x} \, dx + \int_{2n}^{2n+1} \dfrac{1}{x} \,dx \right) &= \sum_{n=1}^{\infty} \left( - \ln (2n) + \ln (2n-1) + \ln(2n+1) - \ln (2n) \right) \\ &= \sum_{n=1}^{\infty} \ln \left( \dfrac{4n^2 -1}{4n^2} \right) \\ &= \ln \left( \prod_{n=1}^{\infty} \dfrac{4n^2 -1}{4n^2} \right) \\ &= \ln \left( \dfrac{2}{\pi} \right) \end{aligned}

which is the reciprocal of the Wallis Product.

Tapas Mazumdar - 3 years, 12 months ago

Log in to reply

Thanks I typed that wrong.

First Last - 3 years, 12 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...